2007
DOI: 10.1111/j.1463-1326.2007.00775.x
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs and the regulation of glucose and lipid metabolism

Abstract: Over recent years, metabolic disorders such as type 2 diabetes have finally become recognized as a major challenge to global health. The attention of scientists therefore has to focus on improving our understanding of the molecular mechanisms behind these diseases and towards the design of new drug therapy strategies. The pathophysiology of diabetes is undoubtedly complex, oftentimes characterized by varying states of insulin resistance and impaired b-cell function; however, the identification of new pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
103
0
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(113 citation statements)
references
References 50 publications
2
103
0
8
Order By: Relevance
“…These alterations are associated with perturbed development and pathological situations. Indeed, miRNAs seem to be major regulators of gene expression in many biological programs, including organ development and metabolism (12)(13)(14)(15)(16)(17). Computational predictions of miRNA targets estimate that a single miRNA can affect a gamut of different mRNAs, suggesting that a large proportion of the transcriptome is subjected to miRNA modulation.…”
mentioning
confidence: 99%
“…These alterations are associated with perturbed development and pathological situations. Indeed, miRNAs seem to be major regulators of gene expression in many biological programs, including organ development and metabolism (12)(13)(14)(15)(16)(17). Computational predictions of miRNA targets estimate that a single miRNA can affect a gamut of different mRNAs, suggesting that a large proportion of the transcriptome is subjected to miRNA modulation.…”
mentioning
confidence: 99%
“…Taken together, it appears that a relatively few miRNAs can regulate as much as 20 -30% of the human genome. Recently, specific miRNAs have been reported to be associated with diabetes (28,29), cancer (30 -33), heart disease (34,35), cell cycle (36), and development (17). Importantly, functional suppression of miRNAs can be achieved, both in vitro and in vivo, by antagomirs, which are chemically engineered oligonucleotides that are antisense to miRNAs (37).…”
mentioning
confidence: 99%
“…Many SNPs located in target sites for miRNA action are correlated with miRNA mediated metabolic disorders like Tourette's Syndrome, Spastic Paraplegia, Hypertension, Parcinson Disease and various types of cancers (Sethupathy & Collins, 2008). MiRNA dysfunction is also correlated with obesity, insulin resistance and type 2 diabetes pathogenesis (Ferland-McCollough et al, 2010;Poy et al, 2007). Genome wide association studies (GWA) as well as meta-analysis studies demonstrated several SNPs correlated with higher risk of type 2 diabetes (Salonen et al, 2007;Zeggini et al, 2008;Dupuis et al, 2010).…”
Section: Snps In Microrna Genes/ Microrna Target Sites and Insulin Rementioning
confidence: 99%